The Shanghai Incident (1932). An Analysis Based on Some New Italian Sources - Rocco Maria Colonna (Nuova Antologia Militare, 2022)
Shanghai has experienced several political and social crises throughout history. This paper aims to reconstruct fully one of the most disruptive of these occurrences: an undeclared war – known as the Shanghai incident – fought by Japanese and Chinese armies over five weeks (28th January – 4th March 1932). In particular, the essay intends to address this matter from a military point of view and therefore tries to retrace all the events of the war carefully (from the initial pretext to the final armistice) and to identify accurately the actual causes and ultimate outcomes of the conflict. Moreover, in the interests of completeness in adding new information, the study considers a broad series of Italian archival documents neglected by the scientific literature.